Intraairway thermal profiles during exercise and hyperventilation in normal man. - McFadden, E R (1985)
When large volumes of air are inhaled at rapid rates of ventilation, substantial segments of the tracheobronchial tree become involved in the conditioning process and the inspirate does not reach body conditions of temperature and humidity until it passes well into the peripheral bronchi. To determine if the manner in which ventilation is elevated is an important factor in producing this response, we measured the temperature of the airstream at six points in the tracheobronchial tree from the pharynx to the subsegmental bronchi during 5 min of exercise and voluntary hyperventilation in seven normal subjects while they inhaled frigid air. Minute ventilation and respiratory frequency were recorded at minute intervals and intrathoracic temperatures were measured continuously. With both forms of hyperpnea, airway temperature fell dramatically, and there were no significant differences between exercise and hyperventilation. These results demonstrate that the thermal events that occur within the lung during short, moderately intense degrees of exercise can be readily simulated by voluntary hyperventilation when ventilation and inspired air conditions are matched. Our data also indicate that this form of exercise does not result in an increase in airstream temperature and raise the possibility that the bronchial blood supply may be determined by the local thermal needs of the airways to recover heat and water independent of, at least moderate, increases in cardiac output.